The nuptial language in “Cántico espiritual”, by San Juan de la Cruz - Josilene Simões Carvalho Bezerra, Cicero Cunha Bezerra (2011)
The Spanish literature of the sixteenth century is deeply marked by the nuptial symbolism expressed in the couple Lover/Beloved. Lyric symbol of the last desire of union of the soul with its love object, that image broke the structure of the courteous poetry and got into the ‘religious’ Renaissance literature. As a model of maximum expression, the Spiritual canticle by San Juan de la Cruz begins with a question: ‘Where, Beloved, did you hide yourself?’ In an erotic game between the Lover and Beloved, there is a question that makes one think about the ‘veiled’ character and secret object of desire, in this case, God. Basically, this is the image of the ‘hidden God’ present in Isaiah (45.15) and which grounds great part of the medieval theological thought, and that in the Renaissance literature finds the way of an ‘ideal’ love, so well represented in the female figures of the great works of chivalry. The aim of this paper is thus to expose the influences and interpretation of the ‘nuptial’ element into San Juan’s text as a fruit of the creative and revolutionary spirit of his poetry.